2001
DOI: 10.1126/science.1063665
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Acrosome Formation in Hrb-Deficient Mice

Abstract: The sperm acrosome is essential for sperm-egg fusion and is often defective in men with nonobstructive infertility. Here we report that male mice with a null mutation in Hrb are infertile and display round-headed spermatozoa that lack an acrosome. In wild-type spermatids, Hrb is associated with the cytosolic surface of proacrosomic transport vesicles that fuse to create a single large acrosomic vesicle at step 3 of spermiogenesis. Although proacrosomic vesicles form in spermatids that lack Hrb, the vesicles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
189
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(192 citation statements)
references
References 9 publications
0
189
0
3
Order By: Relevance
“…Ten genes have been found to be associated with globozoospermia, including Csnk2a2 [30], Hrb [3], Gopc [19], Gba2 [31], Zpbp1 [32], Pick1 [11], Vps54 [27], Hsp90b1 [33], Spaca1 [34] and Dpy19l2 [35]. Among 25%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten genes have been found to be associated with globozoospermia, including Csnk2a2 [30], Hrb [3], Gopc [19], Gba2 [31], Zpbp1 [32], Pick1 [11], Vps54 [27], Hsp90b1 [33], Spaca1 [34] and Dpy19l2 [35]. Among 25%.…”
Section: Discussionmentioning
confidence: 99%
“…Bar indicates 1 µm. them, Hrb [3], GOPC [19], PICK1 [11] and SPACA1 [34] control Golgi-derived vesicle fusion, which is necessary for acrosome formation. We found that GOPC partially colocalized with sp56 on the acrosome during spermatogenesis but failed to be recruited to the acrosome in Atg7-deficient spermatids, suggesting that Atg7 partially regulates GOPC and that both of them are involved in Golgi-derived vesicle fusion and transport to the preacrosome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common region of homozygosity was identified that harbored the gene that encodes aurora kinase C ( AURKC ) at 19q13 in all of these men. It is known to be highly expressed in the testis34, 35 and is putatively involved in cytokinesis, mitosis, and meiosis 36, 37. A single nucleotide deletion (ca 144delC) was detected in the AURKC coding region in all of the patients who were analyzed 33.…”
Section: Culprit Genes That Have Been Identified In Autosomesmentioning
confidence: 99%